Comparative and evolutionary analysis of the reptilian hedgehog gene family (Shh, Dhh, and Ihh) - Xia, Tian (PeerJ, 2019)
The hedgehog signaling pathway plays a vital role in human and animal patterning and cell proliferation during the developmental process. The hedgehog gene family of vertebrate species includes three genes, Shh, Dhh, and Ihh, which possess different functions and expression patterns. Despite the importance of hedgehog genes, genomic evidence of this gene family in reptiles is lacking. In this study, the available genomes of a number of representative reptile species were explored by utilizing adaptive evolutionary analysis methods to characterize the evolutionary patterns of the hedgehog gene family. Altogether, 33 sonic hedgehog (Shh), 25 desert hedgehog (Dhh), and 20 Indian hedgehog (Ihh) genes were obtained from reptiles, and six avian and five mammalian sequences were added to the analysis. The phylogenetic maximum likelihood (ML) tree of the Shh, Dhh, and Ihh genes revealed a similar topology, which is approximately consistent with the traditional taxonomic group. No shared positive selection site was identified by the PAML site model or the three methods in the Data Monkey Server. Branch model and Clade model C analyses revealed that the Dhh and Ihh genes experienced different evolutionary forces in reptiles and other vertebrates, while the Shh gene was not significantly different in terms of selection pressure. The different evolutionary rates of the Dhh and Ihh genes suggest that these genes may be potential contributors to the discrepant sperm and body development of different clades. The different adaptive evolutionary history of the Shh, Dhh, and Ihh genes among reptiles may be due to their different functions in regulating cellular events of development from the embryonic stages to adulthood. Overall, this study has provided meaningful information regarding the evolution of the hedgehog gene family in reptiles and a theoretical foundation for further analyses on the functional and molecular mechanisms that have shaped the reptilian hedgehog genes.